Chirality and the angular momentum of light - Cameron, Robert P. (Philos Trans A Math Phys Eng Sci, 2017)
Chirality is exhibited by objects that cannot be rotated into their mirror images. It is far from obvious that this has anything to do with the angular momentum of light, which owes its existence to rotational symmetries. There is nevertheless a subtle connection between chirality and the angular momentum of light. We demonstrate this connection and, in particular, its significance in the context of chiral light–matter interactions. This article is part of the themed issue ‘Optical orbital angular momentum’.